Sistem Informasi Pengolahan Data Survei untuk Program Pinjaman Usaha Produktif di Koperasi Karyawan Minyak Caltex Rumbai - Yulanda Yulanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Caltex Rumbai Employee Cooperative in Productive Business Loan Program, has utilized technology to facilitate its work. But, the development of technology utilized KKMC still feels less than optimal. The use of paper-based survey forms, puts the risk of damage or loss of data. Unit Savings and Loans re-enter survey data obtained from Surveyor into excel, which makes this activity complicated and takes a long time. It is time for KKMC to build a new system by using an application that can help the data processing of Productive Business Loan survey, this application will use PHP programming language with MySQL database. With this new system can help Unit Saves and Loans and Surveyor in entering data Survey Form and Rooting Profile, and print survey report and Rooting Profile Report Productive Loan Program. Keywords:Information System, Survey, Productive Business Loan.